Long-Term Antitumor Activity and Safety of Enzalutamide Monotherapy in Hormone Naïve Prostate Cancer: 3-Year Open Label Followup Results - Tombal, Bertrand; Borre, Michael; Rathenborg, Per; Werbrouck, Patrick; Van Poppel, Hendrik; Heidenreich, Axel; Iversen, Peter; Braeckman, Johan; Heracek, Jiri; Baron, Benoit; Krivoshik, Andrew; Hirmand, Mohammad; et al. (The Journal of urology, 2018)
PURPOSE: A phase 2 study of enzalutamide monotherapy in patients with hormone naïve prostate cancer demonstrated high prostate specific antigen response rates at 25 weeks, 1 year and 2 years with minimal effects on total body bone mineral density and favorable safety. In this followup analysis we evaluated enzalutamide antitumor activity and safety at 3 years. MATERIALS AND METHODS: In a single arm analysis 67 patients with hormone naïve prostate cancer and noncastrate testosterone (230 ng/dl or greater) received enzalutamide 160 mg per day orally until disease progression or unacceptable toxicity. The primary end point was the prostate specific antigen response (80% or greater decline from baseline). RESULTS: No patients discontinued treatment during year 3. Of 42 patients with prostate specific antigen assessments at 3 years 38 (90.5%, 95% CI 77.4-97.3) maintained a prostate specific antigen response. Of 26 patients with metastases at baseline 17 (65.4%) had a complete or partial response as the best overall response during 3 years. In patients who completed the 3-year visit minimal mean changes from baseline were observed in total body bone mineral density or bone mineral density of the femoral neck, trochanter, spine L1-L4 or forearm (range -2.7% to -0.1%). At 3 years total body fat had increased a mean of 16.5%, total lean body mass had decreased a mean of -6.5% and global health status had minimally decreased from baseline. Common adverse events were gynecomastia, fatigue, hot flush and nipple pain. CONCLUSIONS: Enzalutamide antitumor activity was maintained in patients with hormone naïve prostate cancer at 3 years. Overall bone mineral density, global health status and safety results were similar to those at 2 years.
Keywords: Prostatic Neoplasms; nádory prostaty; bone density; Humans; lidé středního věku; Benzamides; prostate-specific antigen; následné studie; MDV 3100; Aged; Antineoplastic Agents; Phenylthiohydantoin; výsledek terapie; senioři; lidé; Administration, Oral; prostatic neoplasms; nitrily; drug related side effects and adverse reactions; Male; Middle Aged; Treatment Outcome; Aged, 80 and over; protinádorové látky; benzamidy; senioři nad 80 let; fenylthiohydantoin; aplikace orální; mužské pohlaví; Nitriles; Follow-Up Studies